2003
DOI: 10.1063/1.1609043
|View full text |Cite
|
Sign up to set email alerts
|

Electrical contacts to ultrananocrystalline diamond

Abstract: The contact behavior of various metals on n-type nitrogen-doped ultrananocrystalline diamond ͑UNCD͒ thin films has been investigated. The influences of the following parameters on the current-voltage characteristics of the contacts are presented: ͑1͒ electronegativity and work function of various metals, ͑2͒ an oxidizing acid surface cleaning step, and ͑3͒ oxide formation at the film/contact interface. Near-ideal ohmic contacts are formed in every case, while Schottky barrier contacts prove more elusive. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 12 publications
(13 reference statements)
3
26
0
Order By: Relevance
“…Utilization of an n-type nitrogen incorporated UNCD interstitial layer in the device structure suggests the absence of a Schottky barrier at the substrate-diamond interface due to the high nitrogen incorporation and due to the graphitic grain boundaries. 32 In fact, it has been reported that metal contacts to ntype UNCD films are typically ohmic in nature; independent of the metal work function. 33 As the thermionic emission current is affected by device resistivity, the interface electrical resistance of the emitter layer structure may limit the emission.…”
Section: Resultsmentioning
confidence: 99%
“…Utilization of an n-type nitrogen incorporated UNCD interstitial layer in the device structure suggests the absence of a Schottky barrier at the substrate-diamond interface due to the high nitrogen incorporation and due to the graphitic grain boundaries. 32 In fact, it has been reported that metal contacts to ntype UNCD films are typically ohmic in nature; independent of the metal work function. 33 As the thermionic emission current is affected by device resistivity, the interface electrical resistance of the emitter layer structure may limit the emission.…”
Section: Resultsmentioning
confidence: 99%
“…Metallic ohmic contacts were achieved on UNCD surfaces with sputter-deposited Al, Au, Cr, Cu, Pt, and Ti layers, all at a thickness of 200 nm [28], [29]. Currentvoltage contact characteristics were used to calculate layer resistance from the slopes of these curves, including the resistance of the UNCD plus the resistance of the metal contacts themselves.…”
Section: Electrodes and Electrical Contacts To Uncdmentioning
confidence: 99%
“…The growth conditions were as follows: (a) substrate temperature: 800°C; (b) pressure: 200 mbar; (c) microwave power: 1000 W; (d) growth time: 60 min; and (e) gas flow: Ar (98.4 sccm) and CH 4 (1.6 sccm). UNCD films were produced, using the well established Ar-rich/CH4 plasma chemistry developed and extensively used at Argonne National Laboratory [1][2][3][4][5][6][7].…”
Section: Synthesis Of Uncd Filmsmentioning
confidence: 99%
“…UNCD films are grown using Ar-rich [(Ar (99%)/ CH 4 (1%)] plasmas, using Microwave Plasma-Enhanced Chemical Vapor Deposition (MPCVD). UNCD films exhibit a unique set of complementary properties, such as chemical inertness, low friction and high wear resistance, high hardness, and good electrical transport properties when appropriately doped [5][6][7]. Carbon films including diamond and diamond-like carbon (DLC) thin films are also being explored as coatings for artificial joints and artificial heart valves.…”
Section: Introductionmentioning
confidence: 99%